Meglumine: A Novel and Efficient Catalyst for One-Pot, Three-Component Combinatorial Synthesis of Functionalized 2‑Amino‑4H‑pyrans - Guo, Rui-Yun; An, Zhi-Min; Mo, Li-Ping; Wang, Rui-Zhi; Liu, Hong-Xia; Wang, Shu-Xia; Zhang, Zhan-Hui (ACS combinatorial science, 2013)
An efficient one-pot synthesis of functionalized 2-amino-4H-pyrans by a meglumine-catalyzed three-component reaction has been developed. A broad range of substrates including aromatic and heteroaromatic aldehydes, isatin derivatives, and acenaphthenequinone are condensed with enolizable C–H activated compounds and alkylmalonates to give the desired products in high to excellent yields. This methodology provides an alternative approach for rapid access to construct a diversity-oriented library of 4H-pyrans.